Train Network Design With Bus Line and Switching Network Coexisting - Jing WANG; Chao LIU; Jiaying ZHAO; Jiaqi WANG (机车电传动)
In order to meet the increasing demand for data transmission, ensure the reliability and real-time of data transmission, and improve the flexibility and interconnectivity of the train network, a train network control system coexisting with bus and exchange network was designed. The advantages of the two networks were complementary, and the network form could be automatically selected according to the actual situation of the train network and the fault oriented safety principle. A laboratory simulation test platform was built, and the MVB/WTB communication, TRDP communication, the conversion between the two kinds of communication and the train control logic were tested, and the 400 km/h cross-country interconnectivity EMU project verification had been passed. The test results show that the designed network system has excellent performance and can provide important support for the train network control system with more diversified data and more efficient transmission performance.